2008
DOI: 10.1088/0960-1317/18/11/115029
|View full text |Cite
|
Sign up to set email alerts
|

Deep-UV patterning of commercial grade PMMA for low-cost, large-scale microfluidics

Abstract: Although PMMA can be exposed using a variety of exposure sources, deep-UV at 254 nm is of interest because it is relatively inexpensive. Additionally, deep-UV sources can be readily scaled to large area exposures. Moreover, this paper will show that depths of over 100 μm can be created in commercial grade PMMA using an uncollimated source. These depths are sufficient for creating microfluidic channels. This paper will provide measurements of the dissolution depth of commercial grade PMMA as a function of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 33 publications
0
44
0
2
Order By: Relevance
“…Polymeric microfluidic devices can be fabricated by a variety of techniques depending on the intended applications and the equipment available (Haiducu et al 2008;Zhong et al 2010). Polymeric materials of different grades and types are easily available, and the fabrication techniques have saved time and cost compared to glass and silicon-based devices (Song et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Polymeric microfluidic devices can be fabricated by a variety of techniques depending on the intended applications and the equipment available (Haiducu et al 2008;Zhong et al 2010). Polymeric materials of different grades and types are easily available, and the fabrication techniques have saved time and cost compared to glass and silicon-based devices (Song et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study (Kong et al 2006) reported that PC sheets could be UV-lithographied to a depth of 130 nm using the low-pressure mercury lamp as the source. Haiducu et al (2008) also reported that exposure of PMMA sheets to UV-light from a low-pressure mercury lamp resulted in an etched pattern, the depth of which could be developed in isopropanol-water developing solution to decades of micrometers. They ) ascribed the etched depth to the physical shrinkage of the polymer due to the increase in the free volume of the PMMA chains after UV-exposure.…”
Section: Resultsmentioning
confidence: 99%
“…Он обладает достаточно высокой чувствительностью к различного рода излу-чениям, что предопределило его широкое использова-ние как резиста для электронно-лучевой литографии и рентгеновской литографии с высоким разрешени-ем [39,40]. ПММА также применяется в качестве по-зитивного фоторезиста для коротковолнового УФ из-лучения (λ ≤ 300 nm) [41,42], т. е. в области спектра излучения ртутных ламп, которые применялись для облучения образцов в работах [36][37][38].…”
Section: перенос голографической структуры со слоя бхж на пммаunclassified